THE ELECTROSTATIC PROPERTIES OF 1, 2-DIMETHYL-3-NITROBENZENE COMPOUND: ab initio CALCULATION AND X-RAY CHARGE DENSITY ANALYSIS - Chouaih, Abdelkader; Boubegra, N; Megrouss, Y; Boukabcha, N; Hamzaoui, F (Rasayan Journal of Chemistry, 2016)
Electrostatic atomic and molecular properties of the 1, 2-dimethyl-3-nitrobenzene are derived from both experimental data and ab initio theoretical investigation. The molecular dipolar moment obtained by both methods is around 6 Debye and its orientation shows clearly the direction of the intra-molecular charge transfer. The obtained net atomic charges and the derived electrostatic potential show that the electronegative potential is located on the side on the nitro group region whereas the electropositive potential is on the side of the methyl groups. The experimental electrostatic potential is derived from high-resolution single-crystal X-ray diffraction data. The crystallographic investigations are carried out using the multipolar model of Hansen and Coppens in order to take into account the non-spherical part of the atomic electron charge density distribution. In addition to the structural analysis, a thermal motion analysis is carried out in terms of rigid blocks in order to improve the accuracy of obtained results. The experimental results are compared to ab initio theoretical Hartree-Fock (HF) and density functional theory (DFT) predictions, using two different large basis sets. Both DFT and HF calculations gave a molecular dipole moment in good agreement with the extracted one from the X-ray diffraction data (value of 6.57 D). The theoretical investigations are found to reproduce well the experimental molecular electrostatic potential. In the present work, the intermolecular hydrogen bonds are also subjected to a detailed experimental topological analysis.
Keywords: molecular structure; multipolar refinement; hydrogen bonding; thermal motion; dipole moment